Dependence of added mass on cylinder cross-sectional geometry and orientation. (November 2020) - Chen, Guanghao; Alam, Md. Mahbub; Zhou, Yu
Abstract: This paper presents an experimental study on the added masses associated with the cylinders of different cross-sectional geometries (circular, square and rectangular of side ratio of 4) and angles of attack ( θ = 0°- 90°) with respect to incident flow. Two fluid media are considered, i.e. water and paraffin oil. The added mass is investigated from three different perspectives. Firstly, the added mass is estimated from a shift in the oscillation frequency of the cylinder in water or paraffin oil from that in still air, referred to as the average added mass. Thus defined added mass is dependent on both cylinder cross-sectional geometry and orientation but is independent of the fluid medium. The average added mass decreases from 1.52 at θ = 0°to a minimum of 1.20 at θ = 45°for the square cylinder but grows monotonically from 0.55 at θ = 0°to 4.90 at θ = 90°for the rectangular cylinder. Secondly, the added mass is calculated from the equation of structural dynamics. This added mass decreases linearly with the decreasing oscillation amplitude, thus called the amplitude-dependent added mass. Thirdly, the amplitude-dependent added mass is reduced to the unique added mass in the absence of vibration. The unique added mass is in general smaller (< 11.3% depending on geometry and θ ) than the average added mass but displays a similar dependence on the cylinder cross-sectional geometry and θ .